Spatial Distribution Characteristic of Antimony in Typical Paddy Soil of Eastern Hunan Province, China - Wang, ChenRan; Wan, DaJuan; Cao, XueYing; Wang, Huan; Chen, JiaQi; Ouyang, NingXiang; Zhang, YangZhu; Tan, ChangYin (Frontiers in Environmental Science, 2021)
Considering the eastern part of Hunan Province as the research area, 34 sampling sites were set up, 198 samples were collected from representative paddy soil, the distribution characteristics of antimony (Sb) were studied. The results showed that: (1) The content of Sb on the surface of paddy soil ranging from 0.07 to 11.00 mg/kg and the geometric mean was 1.56 mg/kg. (2) The distribution of contents of Sb in paddy soil in different areas was shown as Yueyang > Changsha > Zhuzhou > Xiangtan. (3) Sb showed a strong migration in paddy soil in the research area and its content increased initially and then decreased or gradually decreased with the increase of profile depth. (4) The content of Sb in the substratum was significantly affected by parent materials.